Segmentasi Supplier Mempertimbangkan Kombinasi Purchasing Portfolio Matrix (PPM) - Supplier Portfolio Matrix (SPM) Pada Perusahaan Manufaktur Komponen Otomotif - Rahayu, Siti; Wiyatno, Tri Ngudi (JURNAL TEKNIK INDUSTRI, 2022)
Sustainability of the supply chain is determined by the performance of each partner in the chain. The relationship between buyers and suppliers has an important role in improving supply chain sustainability. Supplier relationship management is one of the most important supply chain related activities for most companies that work with multiple suppliers. The purpose of this study is to present strategies for supplier collaboration and improvement. appropriate supplier development strategies for each dimension are suggested. Purchasing Portfolio Matrix (PPM) - The Supplier Portfolio Matrix (SPM) for supplier segmentation and company executives can have the opportunity to use supplier collaboration and development strategies in the supply chain. Supplier segmentation uses combined PPM-SPM segmentation in the observed Indonesian manufacturing industry to be able to manage supplier relationships. This study proposes an integrative approach that includes supplier risk variables, profit impact, supplier willingness, and supplier ability as criteria for supplier segmentation. The method used in this study is the Best-Worst Method (BWM) to obtain the initial weight of supplier evaluation. The results of this study are recommendations for selecting the appropriate supplier relationship management strategy for each supplier segment.